Regulation of Inhibitory Signaling at the Receptor and Cellular Level; Advances in Our Understanding of GABAergic Neurotransmission and the Mechanisms by Which It Is Disrupted in Epilepsy - Tipton, Allison E.; Russek, Shelley J. (Frontiers in Synaptic Neuroscience, 2022)
Inhibitory signaling in the brain organizes the neural circuits that orchestrate how living creatures interact with the world around them and how they build representations of objects and ideas. Without tight control at multiple points of cellular engagement, the brain’s inhibitory systems would run down and the ability to extract meaningful information from excitatory events would be lost leaving behind a system vulnerable to seizures and to cognitive decline. In this review, we will cover many of the salient features that have emerged regarding the dynamic regulation of inhibitory signaling seen through the lens of cell biology with an emphasis on the major building blocks, the ligand-gated ion channel receptors that are the first transduction point when the neurotransmitter GABA is released into the synapse. Epilepsy association will be used to indicate importance of key proteins and their pathways to brain function and to introduce novel areas for therapeutic intervention.